Business growth strategies for Asia Pacific - Chien, Willie; Shi, Zhenrong, 1944-; Chu, Po-Young. (Singapore ; Hoboken, NJ : Wiley, 2005)
"This book proposes several innovative models and ideas to help readers measure and analyze market opportunities in Asia, and provides valuable insights into consumer behavior, value-chain analysis, innovation capabilities and cost benchmarks within an Asian context. The authors introduce a comprehensive methodology for formulating and implementing a business strategy built around having the right people in the right organizational structure. In adapting Western management theory and practice to the specific needs of the Asian market environment, this book will prove invaluable to anyone wishing to do business in the Asia Pacific region."--BOOK JACKET.
Machine derived contents note: Acknowledgements. -- Foreword. -- Preface. -- List of Abbreviations. -- Introduction. -- Part I: A Macroscopic View Of The Asia Pacific Region. -- Chapter 1. Strategic Viewpoints on Asia Pacific. -- Case Study: GE vs. Haier. -- Chapter 2. Understanding Asian Culture and Business Practice. -- Case Study: Singapore Airline vs. British Airways. -- Chapter 3. Asia Market Opportunities. -- Case Study: Volkswagen vs. Toyota. -- Part Ii: Microscopic View Of The Asia Pacific Region. -- Chapter 4. Analyzing the Competition. -- Case Study: Citigroup vs. HSBC. -- Chapter 5. Technology Factor. -- Case Study: Motorola vs. Samsung Eletronics. -- Chapter 6. Cost Factor. -- Case Study: Dow Chemical vs. Formosa Plastics Group. -- Part Iii: Formulating And Implementing A Strategy For Growth. -- Chapter 7. Formulating a Successful Business Strategy. -- Case Study: TSMCvs. Texas Instrument. -- Chapter 8. Direct Investment and Other Strategic Options. -- Case Study: Nestle;vs. Wahaha. -- Chapter 9. Defining an Effective Asia Pacific Organization. -- Case Study: Dell vs. Foxconn. -- Chapter 10. Managing Human Resources. -- Case Study: Microsoft vs. Wipro. -- Chapter 11. Implementing Business Growth Strategy. -- Case Study: Johnson & Johnson vs. Cipla. -- References and Bibliography. -- Index.
Formerly CIP.
Includes bibliographical references (p. [255]-257) and index.
Keywords: Business planning -- Asia; Business planning -- Pacific Area; Strategic planning -- Asia; Strategic planning -- Pacific Area; Corporations -- Asia -- Growth; Corporations -- Pacific Area -- Growth